2022
DOI: 10.1177/23337214221098900
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Falls, and what are the Circumstances and Consequences of Falls in Community-Dwelling Older Adults Who Need Walking Aids or Home Help Service

Abstract: The objective was to analyze predictive variables for falls in older community-dwelling adults who needed walking aids or home help service, to describe the circumstances and consequences of falls and fall injuries, and to describe the activities preceding falls, n = 175, mean age 83 years. Falls were self-reported monthly in a fall calendar and were followed up by a telephone interview. A logistic regression analysis was performed to investigate predictive baseline variables for falls. Injuries were reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…1 shows the characteristics of the 14 studies. Seven (50%) were nonintervention [25][26][27][28][29][30][31] and seven (50%) were intervention studies [32][33][34][35][36][37][38]. Te 14 studies were conducted in various regions (four each in the US, Asia, and Europe), and the countries where both nonintervention and intervention Home environment safety assessment tool assessed living room (carpet and foor), furniture (bed, chair, and sofa), light (light is bright), bathroom (handrail and antislip mat), kitchen (location of frequently used objects), stairs (safety handrails and outline of the edge), and mobility (shoes and slippers).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 shows the characteristics of the 14 studies. Seven (50%) were nonintervention [25][26][27][28][29][30][31] and seven (50%) were intervention studies [32][33][34][35][36][37][38]. Te 14 studies were conducted in various regions (four each in the US, Asia, and Europe), and the countries where both nonintervention and intervention Home environment safety assessment tool assessed living room (carpet and foor), furniture (bed, chair, and sofa), light (light is bright), bathroom (handrail and antislip mat), kitchen (location of frequently used objects), stairs (safety handrails and outline of the edge), and mobility (shoes and slippers).…”
Section: Search Resultsmentioning
confidence: 99%
“…Regarding environmental risk factors, in fve out of seven studies, the location in the home where most falls occurred was reported. An analysis of nonintervention studies showed that the location where the risk of home falls was emphasized was the bathroom/toilet [25,26,[28][29][30], bedroom [28][29][30], and living room [28][29][30].…”
Section: Environmental Risk Factors Associated With Home Fallsmentioning
confidence: 99%
See 1 more Smart Citation